Inducible glutathione S-transferase (IrGST1) from the tick Ixodes ricinus is a haem-binding protein - Perner, Jan; Kotál, Jan; Hatalová, Tereza; Urbanová, Veronika; Bartošová-Sojková, Pavla; Brophy, Peter M; Kopáček, Petr (Insect biochemistry and molecular biology, 2018)
Blood-feeding parasites are inadvertently exposed to high doses of potentially cytotoxic haem liberated upon host blood digestion. Detoxification of free haem is a special challenge for ticks, which digest haemoglobin intracellularly. Ticks lack a haem catabolic mechanism, mediated by haem oxygenase, and need to dispose of vast majority of acquired haem via its accumulation in haemosomes. The knowledge of individual molecules involved in the maintenance of haem homeostasis in ticks is still rather limited. RNA-seq analyses of the Ixodes ricinus midguts from blood- and serum-fed females identified an abundant transcript of glutathione S-transferase (gst) to be substantially up-regulated in the presence of red blood cells in the diet. Here, we have determined the full sequence of this encoding gene, ir-gst1, and found that it is homologous to the delta-/epsilon-class of GSTs. Phylogenetic analyses across related chelicerates revealed that only one clear IrGST1 orthologue could be found in each available transcriptome from hard and soft ticks. These orthologues create a well-supported clade clearly separated from other ticks' or mites' delta-/epsilon-class GSTs and most likely evolved as an adaptation to tick blood-feeding life style. We have confirmed that IrGST1 expression is induced by dietary haem(oglobin), and not by iron or other components of host blood. Kinetic properties of recombinant IrGST1 were evaluated by model and natural GST substrates. The enzyme was also shown to bind haemin in vitro as evidenced by inhibition assay, VIS spectrophotometry, gel filtration, and affinity chromatography. In the native state, IrGST1 forms a dimer which further polymerises upon binding of excessive amount of haemin molecules. Due to susceptibility of ticks to haem as a signalling molecule, we speculate that the expression of IrGST1 in tick midgut functions as intracellular buffer of labile haem pool to ameliorate its cytotoxic effects upon haemoglobin intracellular hydrolysis.
Keywords: Glutathione Transferase; Ixodes; proteiny členovců; substrátová specifita; Gene Expression Regulation, Enzymologic; klíště; Animals; Hemoglobins; hemoglobiny; glutathiontransferasa; Phylogeny; zvířata; fylogeneze; Substrate Specificity; Arthropod Proteins; regulace genové exprese enzymů